Perhitungan Metode Activity Based Costing untuk Menentukan Tarif Kamar Rawat Inap pada RSUD HAMBA Kabupaten Batanghariupaten Batanghari - Rahmadani, Anjeli Putri; Dewata, Evada; Firmansyah, Firmansyah (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2023)
This community service activity aims to determine inpatient room rates at HAMBA Hospital using the ABC method and to compare the rates set by the hospital using the traditional costing method with ABC. The method of implementing the activity begins with interviews and data analysis in the field with the HAMBA Regional Hospital in Batanghari Regency, the planning and financial divisions and the medical records section. The results of the calculation of the ABC method show that there are distorted costs (undercosting and overcosting). Class I, class II, and class III room rates experienced undercosting, while VIP class experienced overcosting. In the traditional method, the overhead costs for each product are only charged to one cost driver. While the ABC approach explains the cost of each room based on the consumption of each activity and the overhead costs for each product are assigned to various cost drivers, thus making the calculation of the ABC method given in setting inpatient room rates more accurate and precise. Key Word: Activity Based Costing method, inpatient rates